2018
DOI: 10.1017/jwe.2018.36
|View full text |Cite
|
Sign up to set email alerts
|

Does Blind Tasting Work? Investigating the Impact of Training on Blind Tasting Accuracy and Wine Preference

Abstract: We analyzed data from Oxford University Blind Tasting Society's 2018 training season to assess whether blind tasting training improves accuracy. Over time, guesses for grape variety increased in terms of accuracy as well as within-group agreement. Moreover, for grape variety, location, and vintage, the chances of the most common within-group guess being correct were significantly higher than the underlying frequency distribution. Finally, we observed a shift in preference towards older wines, with those with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…This finding relates to a suggestion made by Valentin et al (2007) that beer training influences recognition memory, rather than necessarily enhancing perceptual processes, and may explain why participants commonly fail to generalise their learning to new beers. This contrasts with some research demonstrating that wine training dramatically improves people's ability to detect grape varieties (see Solomon, 1997), but is consistent with other findings in this field showing that training has little influence on taste and olfactory abilities (Wang, Prešern, Fermandes, & Fjaeldstad, 2019;Wang, & Prešern, 2018). The evidence presented here suggests that training allows people to recognise beers, but does not allow them to be able to generalise sufficiently to categorise them.…”
Section: The Effects Of Beer Trainingsupporting
confidence: 78%
“…This finding relates to a suggestion made by Valentin et al (2007) that beer training influences recognition memory, rather than necessarily enhancing perceptual processes, and may explain why participants commonly fail to generalise their learning to new beers. This contrasts with some research demonstrating that wine training dramatically improves people's ability to detect grape varieties (see Solomon, 1997), but is consistent with other findings in this field showing that training has little influence on taste and olfactory abilities (Wang, Prešern, Fermandes, & Fjaeldstad, 2019;Wang, & Prešern, 2018). The evidence presented here suggests that training allows people to recognise beers, but does not allow them to be able to generalise sufficiently to categorise them.…”
Section: The Effects Of Beer Trainingsupporting
confidence: 78%
“…For example, a study with naïve participants who engage in a training procedure similar to that employed by Tempere, Cuzange, Bougeant, Revel, and Sicard (2012) or alternatively with blind‐taste training (cf. Wang & Prešern, 2018) could explore the effect of interference of imagined smells on the recognition of learned odors (similar to Djordjevic, 2004; Djordjevic et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Solomon (1997, Experiment 4) reported PERCEPTUAL LEARNING IN THE CHEMICAL SENSES 12 that experts used an average of five flavour terms whereas intermediates and novices used an average of only 3.1 descriptors. And, more recently, Wang and Prešern (2018) found that experienced wine tasters wrote significantly longer tasting notes (23% longer, on average), than did the novices whom they assessed. Elsewhere, it has been reported that wine experts use more pertinent wine descriptors (Zucco et al, 2011) and, what is more, show a higher degree of consensuality in the terms that they choose to use (Croijmans & Majid, 2016) than do nonexperts.…”
Section: Cognitive / Descriptive Changes In Wine Expertsmentioning
confidence: 98%
“…What is more, research in this area is made all the more confusing as certain authors talk about perceptual learning while actually using a cross-sectional comparison of experts and non-experts. For example, just take approach to the study of perceptual learning has involved measuring the effects of training on, for example, a wine-taster's chemosensory abilities (e.g., Tempere et al, 2012;Walk, 1966;Wang & Prešern, 2018). We will look at the strengths and weakness of each of these approaches in turn.…”
mentioning
confidence: 99%